Exploring the impact of health education on medication adherence and health outcomes in low-income neighborhoods: An observational study - Sandhya Rani M; Ramesh Palabindela; Tejkumar C; Nagendra Naidu B (Asian Journal of Medical Sciences, 2024)
Background: Medication adherence and health outcomes are influenced by multiple factors, including patient education. Aims and Objectives: The aims and objectives of the study are to explore the impact of health education on medication adherence and various health outcomes in low-income neighborhoods. Materials and Methods: An observational study was conducted involving 100 participants from low-income neighborhoods, aged 18–65, who were prescribed at least one chronic medication. Participants underwent a comprehensive health education program focusing on medication adherence, potential side effects, dietary habits, and physical activity. Outcomes were measured using the Morisky Medication Adherence Scale (MMAS-8), biometric values (e.g., blood pressure, blood sugar levels, cholesterol, and body mass index [BMI]), self-reported health status, hospitalization records, medication side-effects awareness, and dietary habits. Results: Post-education, there was a significant improvement in MMAS-8 scores (5.3 pre to 6.8 post, P<0.001). Biometric outcomes revealed a decrease in average blood pressure (from 145/90 mmHg to 130/85 mmHg), fasting blood sugar (from 150 mg/dL to 130 mg/dL), cholesterol levels (from 210 mg/dL to 180 mg/dL), and BMI (from 28.5 to 27.3), all with a statistical significance of P<0.01. Participants reporting “Good” or “Very Good” health increased from 45% to 65%, and those reporting regular physical activity increased from 25% to 45% (P<0.05). Hospitalizations/medical visits decreased from an average of 2.1–1.3 over 6 months (P<0.01). The proportion of participants with awareness of their medication's side effects significantly increased from 30% before the health education program to 70% afterwards (P<0.001). In addition, participants reporting adherence to dietary guidelines rose from 20% to 50% (P<0.01). Conclusion: Health education appears to have a substantial positive impact on medication adherence, biometric health outcomes, and overall well-being in low-income neighborhoods. Structured health education interventions may play a pivotal role in improving community health.